Health Care and Informatics: On IMIA’s Opportunities and Responsibilities in its 5th Decade - Reichertz, Peter L. (Yearbook of Medical Informatics, 2008)
ObjectiveTo report about major past and future activities of IMIA, the International Medical Informatics Association.Method Summarizing discussions and planning activities within IMIA, in particular with respect to its Board and General Assembly meetings in 2007; looking at recent informatics evolution by commenting on IMIA Yearbook surveys and best paper selections.Results Major recent IMIA activities include Medinfo 2007, finalizing its long-term strategic plan ‘Towards IMIA 2015’, and the reinforcement of IMIA’s collaboration with the World Health Organization (WHO). The IMIA Yearbook of Medical Informatics, published annually since 1992, can be regarded as an important observatory for progress in health and biomedical informatics. Future activities comprise implementing IMIA’s strategic plan, reshaping its portfolio of conferences, preparing Medinfo 2010, in addition to continuing to support and enable collaborative international exchange of research and education and bridging to the practice of health and biomedical informatics.Conclusions Informatics has emerged as an increasingly important field for health care and for the health and biomedical sciences. Within the last 40 years IMIA has evolved to a truly global organization, in a world, where medical informatics has gained significant importance for high-quality, efficient health care and for research in biomedicine and in the health sciences. Now in its 5th decade, IMIA’s responsibilities as well as opportunities as a global, independent organization have both increased.Geissbuhler A, Kulikowski C, editors. IMIA Yearbook of Medical Informatics 2008.
Keywords: Medical informatics; health informatics; biomedical informatics; IMIA